Implementation of Public Policy to Achieve Sustainable Development: Challenges and Strategies - Danny Permana (Khazanah Sosial, 2024)
This research aims to analyze and understand various challenges and effective strategies in implementing public policies for sustainable development. The research method used is a descriptive qualitative approach, with data obtained from a review of related literature. The data is processed and analyzed to identify relevant trends and patterns. The research results show that coordination between agencies, adapting policies to local conditions, limited funding, and community participation are the main challenges in policy implementation. Effective strategies include developing cooperation, policy flexibility, innovative funding, and improving communication and public education. Technology, particularly in information and communications, has proven important in increasing transparency and efficiency. Response to climate change and adaptation to global economic and geopolitical challenges are also critical aspects. In conclusion, a collaborative and adaptive approach is needed to overcome these challenges and achieve effective sustainable development.